Some properties of Multiplication Operators acting on Banach spaces of measurable functions (2016)
The purpose of this article is to survey the recent results about the properties of multiplication operators acting on Banach spaces of measurable functions. Most of them was presented by the author in a conference held in Bogotá 2016, on the occasion of celebrating the "IV UN Encuentro de Matemáticas" at the "Universidad Nacional de Colombia".